Pengaruh Latihan Beban Menggunakan Hangboard terhadap Peningkatan Daya Tahan Kekuatan Genggaman Atlet Panjat Tebing - Intan Nurul Faridah; Alen Rismayadi; Geraldi Novian; Fitri Rosdiana (Indonesian Journal of Physical Education and Sport Science, 2025)
Studi purpose. In boulder climbing competitions, most athletes fall because they cannot grip specific holds, preventing them from climbing on sight. This study aims to examine the effect of weight training using a hangboard on improving the grip strength endurance of boulder climbers. Materials and methods. The method used in this study was an experimental method employing a one-group pretest-posttest design. The study population consisted of 10 active athletes from the Indonesian Rock Climbing Federation (FPTI) in Kuningan District, who also served as the study sample using a total sampling technique. The instrument used in this study was the bent-arm hang-open grip test to measure the grip strength endurance of the athletes. Data analysis was performed using SPSS software, including statistical description, normality test, homogeneity test, and hypothesis testing. Results. From the data analysis using hypothesis testing through the Paired Sample T-Test, a significant difference was found between the pre-test and post-test averages in the weight training program using a hang board on the improvement of hand grip strength endurance in boulder climbing athletes, with a difference of 2.35 and a percentage difference of 45% between the pre-test and post-test results. Conclusions. This study concludes that weight training using a hangboard, when performed consistently, can positively impact and significantly improve the grip strength endurance of boulder climbing athletes.